Getting together building relationships as we negotiate - Fisher, Roger 1922-2012; Brown, Scott (Penguin Books, 1989)
Expanding on the principles, insights, and wisdom that made Getting to Yes a worldwide bestseller, Roger Fisher and Scott Brown offer a straightforward approach to creating relationships that can deal with difficulties as they arise. Getting Together takes you step-by-step through initiating, negotiating, and sustaining relationships.